Facet engineering in metal organic frameworks to improve their electrochemical activity for water oxidation. Issue 31 (18th March 2020) - Wan, Jiawei; Liu, Di; Xiao, Hai; Rong, Hongpan; Guan, Sheng; Xie, Feng; Wang, Dingsheng; Li, Yadong
Abstract : We present a facile and low-cost method to shape ZIF into 2D nanosheets with exposed (002) facets and discover that they exhibit excellent activity for oxygen evolution reaction. Abstract : The facet effect has been well demonstrated for nanocrystal catalysis, however it is rarely revealed in metal organic frameworks (MOFs). Herein, we present a facile way to construct 2D zeolitic imidazolate framework-67 (ZIF-67) with dominant exposure of the (002) facets. We discovered that the ZIF-67 (002) facet exhibited the highest catalytic activity for oxygen evolution reaction (OER) among the (002), (011), and (111) facets. Moreover, this facet engineering is also available for ZIF-8 nanocrystals.